Thermoneutrality but Not UCP1 Deficiency Suppresses Monocyte Mobilization Into Blood. Issue 6 (1st September 2017) - Williams, Jesse W.; Elvington, Andrew; Ivanov, Stoyan; Kessler, Skyler; Luehmann, Hannah; Baba, Osamu; Saunders, Brian T.; Kim, Ki-Wook; Johnson, Michael W.; Craft, Clarissa S.; Choi, Jae-Hoon; Sorci-Thomas, Mary G.; et al.
Abstract : Rationale: : Ambient temperature is a risk factor for cardiovascular disease. Cold weather increases cardiovascular events, but paradoxically, cold exposure is metabolically protective because of UCP1 (uncoupling protein 1)-dependent thermogenesis. Objective: : We sought to determine the differential effects of ambient environmental temperature challenge and UCP1 activation in relation to cardiovascular disease progression. Methods and Results: : Using mouse models of atherosclerosis housed at 3 different ambient temperatures, we observed that cold temperature enhanced, whereas thermoneutral housing temperature inhibited atherosclerotic plaque growth, as did deficiency in UCP1. However, whereas UCP1 deficiency promoted poor glucose tolerance, thermoneutral housing enhanced glucose tolerance, and this effect held even in the context of UCP1 deficiency. In conditions of thermoneutrality, but not UCP1 deficiency, circulating monocyte counts were reduced, likely accounting for fewer monocytes entering plaques. Reductions in circulating blood monocytes were also found in a large human cohort in correlation with environmental temperature. By contrast, reduced plaque growth in mice lacking UCP1 was linked to lower cholesterol. Through application of a positron emission tomographic tracer to track CCR2 + cell localization and intravital 2-photon imaging of bone marrow, we associated thermoneutrality with an increased monocyte retention in bone marrow. Pharmacological activation of β3-adrenergic receptors applied to mice housed at thermoneutrality induced UCP1 in beige fat pads but failed to promote monocyte egress from the marrow. Conclusions: : Warm ambient temperature is, like UCP1 deficiency, atheroprotective, but the mechanisms of action differ. Thermoneutrality associates with reduced monocyte egress from the bone marrow in a UCP1-dependent manner in mice and likewise may also suppress blood monocyte counts in man. Abstract : Supplemental Digital Content is available in the text.